2014
DOI: 10.1016/j.contraception.2014.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve adolescents' contraceptive behaviors in low- and middle-income countries: a review of the evidence base

Abstract: Though the evidence base is weak, there are promising foundations for adolescent contraceptive interventions in nearly every region of the world. We offer recommendations for programmers and identify gaps in the evidence base to guide future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 24 publications
2
46
0
2
Order By: Relevance
“…In Ghana, Opoku (2010) and Hindin, McGough, and Adanu (2014) have reported similar barriers to condom use, including shyness in buying contraceptives, the cost of contraceptives, and non-youth friendly health services being barriers to access. Two recent reviews show the critical importance of changing selfefficacy and behavioural control beliefs in increasing young people's condom use (Gottschalk and Ortayli 2014;Napierala Mavedzenge, Doyle, and Ross 2011). Our results suggest that changing efficacy beliefs towards buying and negotiating condom use among young women could be a useful focus of future interventions aiming at preventing teenage pregnancies in Ghana.…”
Section: Discussionmentioning
confidence: 83%
“…In Ghana, Opoku (2010) and Hindin, McGough, and Adanu (2014) have reported similar barriers to condom use, including shyness in buying contraceptives, the cost of contraceptives, and non-youth friendly health services being barriers to access. Two recent reviews show the critical importance of changing selfefficacy and behavioural control beliefs in increasing young people's condom use (Gottschalk and Ortayli 2014;Napierala Mavedzenge, Doyle, and Ross 2011). Our results suggest that changing efficacy beliefs towards buying and negotiating condom use among young women could be a useful focus of future interventions aiming at preventing teenage pregnancies in Ghana.…”
Section: Discussionmentioning
confidence: 83%
“…[30] A literature review on the topic reported that most interventions to improve adolescent access to care focused on making services more adolescent-friendly, including provider awareness of adolescents’ needs and barriers to care, counseling skills and providing privacy and confidentiality. [32] An analysis of nationally representative survey data about family planning quality-of-care from the healthcare user’s perspective in Mexico found that adolescent and younger women (15–24 years) were less likely to receive high quality care than adult women (25–29 years). [33]…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from reviews and studies that fed into the WHO Guidelines “Preventing Early Pregnancy and Poor Reproductive Outcomes Among Adolescents” as well as subsequent systematic reviews point to the factors that contribute to improved contraceptive access to adolescents [14–16]. For planning purposes, it is useful to conceptualize these factors into those that are supply and demand, as some frameworks have done [17, 18].…”
Section: Introductionmentioning
confidence: 99%